1993
DOI: 10.1101/gad.7.12b.2598
|View full text |Cite
|
Sign up to set email alerts
|

General splicing factor SF2/ASF promotes alternative splicing by binding to an exonic splicing enhancer.

Abstract: The general splicing factor SF2/ASF binds in a sequence-specific manner to a pm~ne-dch exonic splicing enhancer {ESE) in the last exon of bovine growth hormone (bGH) pre-mRNA. More importantly, SF2/ASF stimulates in vitro splicing of bGH intron D through specific interaction with the ESE sequences. However, another general splicing factor, SC35, does not bind the ESE sequences and has no effect on bGH intron D splicing. Thus, one possible function of SF2/ASF in alternative and, perhaps, constitutive pre-mRNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
268
2
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(286 citation statements)
references
References 43 publications
12
268
2
3
Order By: Relevance
“…SR proteins have been observed to in¯uence splicing activity via their binding to both splice sites and special splicing accessory sequences known as enhancers (Zahler et al, 1993b;Fu, 1995;Manley and Tacke, 1996;Valcarcel and Green, 1996). Recent studies have indicated substrate-speci®c binding and activity for individual SR proteins (Fu, 1993;Sun et al, 1993;Zahler et al, 1993a;Ca ceres et al, 1994;Wang and Manley, 1995;Chandler et al, 1997;Liu et al, 1998). Furthermore, individual SR proteins have distinct tissue distributions (Zahler et al, 1992;Screaton et al, 1995;Ca ceres and Krainer, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…SR proteins have been observed to in¯uence splicing activity via their binding to both splice sites and special splicing accessory sequences known as enhancers (Zahler et al, 1993b;Fu, 1995;Manley and Tacke, 1996;Valcarcel and Green, 1996). Recent studies have indicated substrate-speci®c binding and activity for individual SR proteins (Fu, 1993;Sun et al, 1993;Zahler et al, 1993a;Ca ceres et al, 1994;Wang and Manley, 1995;Chandler et al, 1997;Liu et al, 1998). Furthermore, individual SR proteins have distinct tissue distributions (Zahler et al, 1992;Screaton et al, 1995;Ca ceres and Krainer, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…SF2/ASF and SC35, two SR proteins, differ in their ability to commit different pre-mRNAs to the splicing pathway (18). SF2/ASF, but not SC35, recognized sequences very similar to purine-rich elements found in various natural splicing enhancers (9,19). SRp40, another member of the SR protein group, binds specific ESE, and one study showed that phosphorylation of the arginrine/serine-rich domain is necessary for sequence-specific binding (20).…”
mentioning
confidence: 99%
“…For example, a majority of exonic splicing enhancer (ESE) 1 elements have been reported to be abundant in purine nucleotides (14,15), and these elements have been shown to bind the splicing factor for control of alternative splicing. Serine/arginine-rich (SR) proteins, a group of splicing factors, play important roles both in ESE-independent and ESE-dependent splicing (8,9,16,17). SR proteins show RNA binding activity to each cis-acting element, as well as protein-protein interaction activity in the formation of a commitment complex of spliceosome (16).…”
mentioning
confidence: 99%
“…Several classes of ESEs have been shown to bind SR (serine/arginine-rich) proteins (Lavigueur et al 1993;Sun et al 1993;Tian and Maniatis 1993). The mammalian SR protein family consists of 10 core members, not including isoforms (Screaton et al 1995) or related genes (Tupler et al 2001).…”
mentioning
confidence: 99%